2018
DOI: 10.2134/jeq2018.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Molybdenum Adsorption and Desorption in Soils

Abstract: Much uncertainty exists in mechanisms and kinetics controlling the adsorption and desorption of molybdenum (Mo) in the soil environment. To investigate the characteristics of Mo adsorption and desorption and predict Mo behavior in the vadose zone, kinetic batch experiments were performed using three soils: Webster loam, Windsor sand and Mahan sand. Adsorption isotherms for Mo were strongly nonlinear for all three soils. Strong kinetic adsorption of Mo by all soils was also observed, where the rate of retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…Moreover, K f values decreased from 294.9 L kg −1 at pH 4.0 to 8.7 L kg −1 at pH 7.5, resulting from the decreased amount of adsorption. This is consistent with our previous study that there was a significantly negative relation between solution pH and K f (Sun and Selim, 2018). The Langmuir equation S / S max = ω C /(1+ω C ) is another commonly used equilibrium sorption model, where S max (mg kg −1 ) represented maximum sorption capacity and ω (L mg −1 ) is a Langmuir coefficient related to the binding strength.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…Moreover, K f values decreased from 294.9 L kg −1 at pH 4.0 to 8.7 L kg −1 at pH 7.5, resulting from the decreased amount of adsorption. This is consistent with our previous study that there was a significantly negative relation between solution pH and K f (Sun and Selim, 2018). The Langmuir equation S / S max = ω C /(1+ω C ) is another commonly used equilibrium sorption model, where S max (mg kg −1 ) represented maximum sorption capacity and ω (L mg −1 ) is a Langmuir coefficient related to the binding strength.…”
Section: Resultssupporting
confidence: 94%
“…They suggested that Mo adsorption on oxides increased from pH 2 to 4, exhibited a peak near pH 4, and decreased with increasing pH above 4. Recently, Sun and Selim (2018) found that Mo(VI) sorption capacity and kinetic rate on an acidic soil was much higher than that of a neutral soil. It is commonly accepted that the maximum in the adsorption of anions occurs at pH values close to their dissociation constants (p K ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is well established that both V and phosphate are specifically retained on mineral via similar inner‐sphere surface complexes (Arai and Sparks, 2001; Rahnemaie et al, 2007; Larsson et al, 2017a). Moreover, Freundlich N is a measure of the extent of heterogeneity of the sorption sites having different affinities for solute retention by matrix surfaces (Kinniburgh, 1986; Ho et al, 2002; Sun and Selim, 2018). In this study, although the N values increased with increasing applied phosphate concentrations, they did not vary significantly among all three applied phosphate concentrations ( p > 0.05).…”
Section: Resuls and Discussionmentioning
confidence: 99%